2005
DOI: 10.1021/jf0484273
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Acids Enzymatic Lipophilization

Abstract: Lipophilization is the esterification of a lipophilic moiety (fatty acid or fatty alcohol) on different substrates (phenolic acid, sugar, protein, ...), resulting in new molecules with modified hydrophilic/lipophilic balance. This reaction can be obtained chemically or enzymatically using different enzymes. Phenolic acids possess interesting biological properties (antioxidant, chelator, free radical scavenger, UV filter, antimicrobial, ...), but because of their relatively low solubility in aprotic media, thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
148
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(164 citation statements)
references
References 52 publications
4
148
0
8
Order By: Relevance
“…Thus, there is a technical dilemma in choosing an effective system in which a polar substrate (e.g. phenolics) and nonpolar (a long chain alcohol, for example) will have both high solubility and where the enzymes maintain a good activity (Figueroa-Espinoza and Villeneuve, 2005). Nevertheless, there are some reports dealing with esterification of phenolic acids with fatty alcohols in organic solvents, solvent-free conditions (the role of which was ensured by the excess of alcohol) or in IL (Pang et al, 2013;Weitkamp et al, 2006;Yang et al, 2012).…”
Section: Lttm a New Family Of Promising Green Mediamentioning
confidence: 99%
“…Thus, there is a technical dilemma in choosing an effective system in which a polar substrate (e.g. phenolics) and nonpolar (a long chain alcohol, for example) will have both high solubility and where the enzymes maintain a good activity (Figueroa-Espinoza and Villeneuve, 2005). Nevertheless, there are some reports dealing with esterification of phenolic acids with fatty alcohols in organic solvents, solvent-free conditions (the role of which was ensured by the excess of alcohol) or in IL (Pang et al, 2013;Weitkamp et al, 2006;Yang et al, 2012).…”
Section: Lttm a New Family Of Promising Green Mediamentioning
confidence: 99%
“…However, their applications in oil-based food processing and cosmetic industries are limited due to their low solubility in hydrophobic media (Buisman et al, 1998;Figueroa-Espinoza and Villeneuve 2005). To improve the lipophilicity of phenolic acids, an alternative method is incorporation of phenolic acids into triacylglycerols through enzymatic reactions (Compton et al 2000;Sabally et al 2005Sabally et al , 2006Sabally et al , 2007Laszlo and Compton 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the lipophilicity of phenolic acids, an alternative method is incorporation of phenolic acids into triacylglycerols through enzymatic reactions (Compton et al 2000;Sabally et al 2005Sabally et al , 2006Sabally et al , 2007Laszlo and Compton 2006). However, direct transesterification of phenolic acids with triacylglycerols is generally suffered from long reaction time and low efficiency (Figueroa-Espinoza and Villeneuve 2005;Compton et al 2000). Thus, many efforts, for example, through medium engineering to improve solubility of phenolic acids (Sabally et al 2006;Lue et al 2005), and through chemoenzymatic approach (Sun et al, 2009), have been made to improve the efficiency of related reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Their biological properties, particularly the antioxidant activity, are well known and depend on the structural characteristics of these compounds (Nenadis et al 2004). Because of their relative polar properties, important efforts have been made in order to increase their hydrophobicity and therefore produce amphiphilic molecules of industrial value (Figueroa-Espinoza and Villeneuve, 2005). Thus, esters of hydro-p-coumaric (Lee et al 2003), hydroferulic (Hegazi and El Hady, 2002) and hydrocaffeic (Silva et al 2000) acids, as well as alkyl coumarates (Tapia et al 2004) and ferulates (Ou and Kwok, 2004), have been widely reported as antioxidants in food, cosmetic and pharmaceutical formulations.…”
mentioning
confidence: 99%
“…In spite of the remarkable industrial potential of phenylpropanoid acid esters as food antioxidants, their use in oil-based food processing has been limited, because of their high water solubility (Figueroa-Espinoza and Villeneuve, 2005). Thus, several methods have been proposed in order to obtain hydrophobic derivatives of phenylpropanoid acids.…”
mentioning
confidence: 99%